2019
DOI: 10.3390/jcm8020254
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Real-World Effectiveness of Trastuzumab in Breast Cancer

Abstract: Trastuzumab is a milestone in the treatment of human epidermal growth factor receptor 2 positive (HER2+) breast cancer (BC), in both the early and metastatic settings. Over the last two decades, clinical trials have established the good safety profile of trastuzumab. Cardiotoxicity remains the most frequent adverse event, more commonly exemplified by an asymptomatic decline in the left ventricular ejection fraction rather than congestive heart failure. Results from several long-term (>5 years) safety analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Obviously, due to its shorter duration, 6 months of trastuzumab would cost less money compared with 12 months. In addition, a recent study from Iran indicated that 6 months of trastuzumab was a more cost-effective choice than 12 months, with far less incremental spending (8,826 vs. 18,588 pounds) (35). As a result, 6 months of trastuzumab might decrease the financial pressure on thousands of families using trastuzumab, and reduce their psychological burdens in the face of huge medical costs; this shorter duration of trastuzumab is more likely to be affordable for patients in low-and middle-income countries who lack sufficient medical funds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, due to its shorter duration, 6 months of trastuzumab would cost less money compared with 12 months. In addition, a recent study from Iran indicated that 6 months of trastuzumab was a more cost-effective choice than 12 months, with far less incremental spending (8,826 vs. 18,588 pounds) (35). As a result, 6 months of trastuzumab might decrease the financial pressure on thousands of families using trastuzumab, and reduce their psychological burdens in the face of huge medical costs; this shorter duration of trastuzumab is more likely to be affordable for patients in low-and middle-income countries who lack sufficient medical funds.…”
Section: Discussionmentioning
confidence: 99%
“…Trastuzumab is a type of monoclonal antibody against the HER2 receptor, and it is usually combined with other antitumor drugs for the treatment of breast carcinomas and gastric carcinomas (3). In nearly two decades, some studies have suggested that trastuzumab combined with chemotherapy may remarkably decrease the risk of relapses and/or metastasis and improve the survival of women with HER2+ breast cancer (4)(5)(6)(7)(8). Additionally, 1 year of trastuzumab has been commonly used as the standard duration in patients with HER2+ early-stage breast cancer (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…[32] Mass spectrometry (MS) measured m/z 8077. 5 Figure 2) After diluted with 10mL deionized water, the complex was puri ed by a Varian BOND ELUT C18 column. After washing with 10 mL deionized water again, the product was eluted with 0.3mL10 mM HCl in ethanol.…”
Section: A Body Conjugationmentioning
confidence: 99%
“…[2][3][4] Monoclonal antibodies, including trastuzumab and pertuzumab etc have been used for therapy of HER2-positive cancers. [5][6][7] Current selection of patients for targeted therapy is mainly dependent on the status of HER2, which was determined by biopsy using immunohistochemistry or uorescence in situ hybridization. [8] However, the invasive method may not be reliable because the HER2 expression is heterogeneous in the tumors and varies during the progress of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Monoclonal antibodies such as trastuzumab and pertuzumab etc have been approved for the treatment of HER2-positive cancers and the efficacy is satisfactory. [5][6][7] The current selection of patients for HER2 targeted therapy is mainly dependent on the HER2 status determined by biopsy using immunohistochemistry or fluorescence in situ hybridization. [8] However, the invasive method may not be reliable due to the heterogeneous expression of the receptor and its dynamic changes during the progress of the disease.…”
Section: Introductionmentioning
confidence: 99%